304PSurvival outcomes and survival predictors in recurrent and metastatic head and neck squamous cell cancer (R/M-HNSCC) patients treated with chemotherapy (CT) plus cetuximab as first-line therapy in a real-world study. (24th November 2019) - Pontes, F; Rego, I; Domingues, I C; Pinto, L; Garcia, R; Teixeira, M M; Serra, T; Khoury, L; Mariano, M; Sousa, G M
Abstract: Background: The EXTREME trial demonstrated that patients with R/M-HNSCC benefit from the addition of cetuximab to first-line platinum-based CT in relation to overall survival (OS), progression-free survival (PFS) and response rate. The aims of the study are to evaluate the survival outcomes and identify predictors of survival among these patients (pts). Methods: Data regarding R/M HNSCC consecutive pts treated with cetuximab and platinum from 2009 to 2018 were retrospectively collected. The analyses of response (R.), PFS and OS, each evaluated starting from first treatment, were performed. A Cox proportional hazard model was run and Survival curves were estimated with the Kaplan-Meier method and compared using the log-rank test. Results: 108 pts were identified with ECOG-PS 0-1. Median age was 57 years (y.) (36-74y.) Primary tumor sites were oropharynx 28(25, 9%), oral cavity 19 (17, 6%), larynx/hypopharynx 57 (52, 7%) and others 4 (3, 7%). Median OS was 16, 9 months (m). (95% confidence interval [CI] 12, 9-20, 9), and mean PFS was 7, 4 m. (95% CI 4, 1-8, 9). 43 pts (39, 8%) completed 6 cycles of treatment. R. rate (partial R. and complete R.) was 19%, with 31 (28, 7%) showing stable disease. ECOG-PS 1 (HR = 1.71, 95% CI 1, 1-2, 97) and the location of the primary tumor in the larynx/hypopharynx (HR = 1.98, 95% CI 1, 14-3, 48) were significantly associated with an increased risk of disease progression.48 (44%) pts who received CT plus cetuximab continued to receive cetuximab until disease progression or unacceptable toxic effects with statistical significant differences between this sub-group and those who weren't able to receive Cetuximab monotherapy (OS 23, 6m. (95% CI 16, 1-31, 1) vs 10, 9 m. (95% CI 8, 7-13, 1) p = 0, 001). OS was higher in pts with grade 2-4 skin toxicity associated with cetuximab (OS 18, 4m. (95% CI 13.7-23.1) vs 13, 7m. (95% CI 8, 7-18, 8) p = 0.05). Conclusions: In non-selected R/M HNSCC pts, we obtained a median PFS and OS of 7, 4 and 16, 9 months, superior to 5, 6 and 10, 1 months reported in Extreme trial (Vermorken et al. 2008). ECOG PS, larynx/hypopharynx location and skin toxicity related to Cetuximab could be used to define pt prognosis. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.